DIPG-11. ACTIVATION OF RAS SIGNALING AND DISTINCT MITOGEN-ACTIVATED PROTEIN KINASES (MAPKs) PROVIDES UNIQUE THERAPEUTIC VULNERABILITIES IN MUTANT HISTONE DIPG. (23rd April 2019) - Koncar, Robert; Stanton, Ann-Catherine; Dey, Brittany; Agrawal, Nishant; Wassell, Michelle; McCarl, Lauren; Locke, Abigail; Sanders, Lauren; Vaske, Olena Morozova; Kohanbash, Gary; Felker, James; James, C David; et al.
Abstract: Diffuse intrinsic pontine gliomas (DIPGs) are incurable pediatric brain tumors with an aggressive onset. Apart from irradiation, there are currently no effective therapies available for DIPG patients, who have a median survival time of less than one year. DIPG cells possess a mutation in histone H3 (H3K27M) that results in a reduction of H3K27 trimethylation and activation of oncogenic signaling pathways. We show that the H3K27M mutation induces RAS pathway signaling which is augmented by additional RAS activators including PDGFRA. We observed that the H3K27M mutation leads to silencing of GTPase-activating proteins, namely RASAL1, which when ectopically expressed, reduced proliferation and RAS activation. An siRNA screen of RAS pathway effectors identified ERK5, but not ERK1/2, as important for DIPG growth. Suppression of ERK5, which is highly expressed in DIPG, decreased DIPG cell proliferation and induced apoptosis both in vitro and in vivo. Mechanistically, we show that ERK5 directly activates and stabilizes the proto-oncogene MYC. ERK5 overexpression fully rescued ERK5-depleted cells and partial rescue was achieved by expression of ERK5 mutants lacking kinase activity or the transactivation domain (ΔTAD). However, no rescue was achieved with kinase-dead, ΔTAD double mutants. Additionally, ERK5 knockdown or treatment with ERK5 inhibitors significantly increased survival of mice intracranially engrafted with DIPG cells. TG02, a pan-CDK and ERK5 inhibitor currently in phase II trials for various cancers, was the most effective treatment, extending median survival time nearly two-fold. Collectively, our data demonstrate DIPG reliance on RAS and MYC activities, and in so doing reveal novel therapeutic targets for treating these tumors.